Selective feeding in Southern Ocean key grazers—diet composition of krill and salps - Nora-Charlotte Pauli (Nature Portfolio, 2021)
In this manuscript, Pauli et al. directly compare the diets of two key Southern Ocean grazers, krill and salps. The 18S profiles of diet and pellets from both species do not match the planktonic profile, suggesting that both are selective grazers with a similar diet.